Firm expectations and news: micro v macro - Born, Benjamin; Enders, Zeno; Menkhoff, Manuel; Müller, Gernot J.; Niemann, Knut (CESifo working papers, 2022)
In this study, we investigate how firm expectations about their own developments respond to different types of news. We classify news as either micro or macro, with micro news being information about firm-specific developments and macro news being information about the aggregate economy. Our analysis of firm surveys from Germany and Italy shows that both types of news consistently predict forecast errors, contradicting the idea of full-information rational expectations. Yet while firm expectations overreact to micro news, they underreact to macro news. We propose a model in which firms suffer from "island illusion" to explain these patterns in the data.
Keywords: Graue Literatur